Case Report: Cutaneous Pleomorphic Lymphangiosarcoma in a Dog Exhibiting Features of Human Composite Hemangioendothelioma - Cook, Matthew R.; Lorbach, Joshua N.; White, Mary E.; Zann, Geoffrey J.; Cianciolo, Rachel E.; Selmic, Laura E.; Wavreille, Vincent; Kisseberth, William C. (Frontiers in Veterinary Science, 2021)
Angiosarcomas are a broad category of neoplasms originating from the vasculature. Lymphangiosarcoma (LAS) is an uncommon type of angiosarcoma reported in humans and canines arising from lymphatic endothelium. LAS can be differentiated from other angiosarcomas in dogs based on expression of Prospero-related homeobox gene-1 (PROX-1) or lymphatic vessel endothelial receptor-1 (LYVE-1). Composite hemangioendothelioma is a rare angiosarcoma subtype described in people and characterized by a variable biologic behavior and infrequent metastasis. This variant of angiosarcoma histologically combines features of retiform hemangioendotheliomas (RH) and epithelioid hemangioendothelioma. Information regarding the cytologic and histopathologic appearance and clinical course of dogs with this neoplasm is unknown. A 10-year-old intact male Labrador retriever presented with a 6 cm diameter cutaneous mass caudal to the left elbow that was progressively growing over 1.5 years. On physical examination, palpable extensions were identified coursing proximally over the triceps with concurrent loco-regional peripheral lymphadenopathy. Fine needle aspirates (FNA) and cytologic assessment of the cutaneous mass, left prescapular, and accessory axillary lymph nodes reported that this appeared to be a metastatic epithelial neoplasm, although a mixed carcinoma or collision tumor could not be excluded. A biopsy of the mass was submitted for histopathology and was consistent with a well-differentiated angiosarcoma with features of composite hemangioendothelioma. The neoplasm expressed vimentin, CD31, von Willebrand factor (vWf), and PROX-1, supporting the diagnosis of lymphangiosarcoma. Complete staging was performed and no additional metastatic lesions were identified. Left forelimb amputation and lymph node extirpation were performed. Based on the diagnosis of metastatic lymphangiosarcoma, doxorubicin chemotherapy was administered. Seven months post-amputation, the tumor reoccurred at the amputation site without evidence of metastatic disease. This report describes a malignant, locally aggressive lymphatic origin vascular tumor in a dog, with features consistent with descriptions of composite hemangioendothelioma in humans. Cytologic features in this case were discordant with its true mesenchymal etiology, obfuscating diagnosis. The morphologic features of the mesenchymal neoplastic population and immunohistochemistry (IHC) labeling ultimately supported a diagnosis of pleomorphic lymphangiosarcoma with features of composite hemangioendothelioma.